PERANAN KOMPENSASI PKWT DAN BONUS AKHIR TAHUN DALAM MENINGKATKAN KINERJA KARYAWAN PADA PT. SURYARAYA RUBBERINDO INDUSTRIES - Muhammad Ferdy Ramdhan Rifulton; Mega Puspita Sari (Jurnal Ilmiah Global Education, 2023)
This study aims to determine the role of PKWT compensation and year-end bonuses in improving employee performance at PT Suryaraya Rubberindo Industries. This research uses descriptive qualitative research methods. Respondents in this study were 15 respondents consisting of contract employees of the wrapping & setting division of the packing section of PT Suryaraya Rubberindo Industries. The data collection methods used are observation, interview, and documentation. The data collected were analyzed descriptively by reducing data, presenting data, and drawing conclusions. The results of this study indicate that "The Role of PKWT Compensation and Year-End Bonus in Improving Performance in Employees of PT Suryaraya Rubberindo Industries" has a good role, as evidenced by the results of research from 4 PKWT compensation indicators, namely the first is wages & salaries that are by the contract employees want but need to be reviewed again regarding the adjustment of the value of wages & salaries between government and company policies. Furthermore, the second is incentives. The incentives of non-permanent contract employees carried out by the company can improve their performance in a job. Moreover, the third is the PKWT allowance, which benefits when someone has ended their tenure at the company so that the money can be used for daily needs or business capital. Then, some employees consider that "PKWT allowances" and other benefits can help with wages & salaries, which for some employees are still insufficient. Furthermore, the fourth is that the facilities in the company are sufficient for the needs of contract employees and need a little attention to safety & risk in the work area.